Information System Introduction and Sales of Furniture Products in Mebel Berkah Indramayu Regency Using the Web - Nursadi, Nursadi; Minah Jaya, Suhana (Jurnal Improsci, 2023)
This research aims to create a computerized product recognition and sales system using the Mebel Berkah Indramayu Regency website. For a proliferating company such as Mebel Berkah Kabupaten Indramayu, one of the leading furniture companies in Indramayu that produces national quality indoor and outdoor furniture, processing safe, fast, and accurate information systems is essential. Unfortunately, the use of information technology in Indramayu Regency Blessing Furniture is not optimal. The method used is descriptive qualitative because it describes or analyzes a research result but is not used to make broader conclusions. The result is that when the application is first run, a splash screen will appear. The splash screen is the opening screen for this application. During the splash screen, the system also reads data from the database server stored in the MySQL database using a web service as a connecting bridge.